Factors Influencing the Diffusion of Blockchain Technology in the Indonesian Goverment - Noman, Eltyasar Putrajati; Gwenhure, Anderson Kevin (Journal of Information Systems Engineering and Business Intelligence, 2025)
Background: Blockchain can improve the security and efficiency of government information systems. However, the adoption of this technology in Indonesia is still limited, especially in the government sector. Previous studies have emphasized the importance of regulatory and legal aspects in blockchain implementation. This condition is a challenge and an opportunity to examine the factors that influence the diffusion of blockchain innovation in the Indonesian government.  Objective: This study aims to identify and analyze the factors that influence the diffusion of blockchain technology in the Indonesian government through hypothesis testing and conceptual model development, as well as to determine the current stage of blockchain technology diffusion in the Indonesian government.  Methods: This study uses data from a questionnaire survey of 24 government agencies in Indonesia, representing various levels of central, provincial, district, and city, and focusing on the technology sector. A total of 192 responses were successfully collected. The collected data were analyzed using SmartPLS software to test the validity and reliability of the instrument, research hypothesis, and proposed conceptual model, and the results of the hypothesis test were used to determine the current stage of blockchain technology diffusion in the Indonesian government.  Results: The study's results indicate that the research instruments used are valid and reliable and meet the requirements for use in this study. Of the eight hypotheses proposed, three were accepted, and five were rejected. The tested conceptual model showed good agreement with the empirical data.  Conclusion: This study concludes that relative advantage and stakeholder roles are key factors significantly influencing the Indonesian government's intention to adopt blockchain technology. In contrast, complexity, regulation, top management support, and competence do not significantly influence adoption intentions. The diffusion of blockchain technology in the Indonesian government is still in the knowledge stage, so the decision to adopt it has not been reached. The implication is that the government needs to prioritize blockchain advantages and actively involve stakeholders, such as experts and developers, in efforts to adopt this technology.  Keywords: Diffusion of Innovation, Blockchain, Information Systems, E-Government, Information Technology Management